Xylan degrading enzymes from fungal sources - Kirikyali, N.; Connerton, Ian F. (SciTechnol, 2015)
Fungi have the ability to degrade xylan as the major component of plant cell wall hemicellulose. Fungi have evolved batteries of xylanolytic enzymes that concertedly act to depolymerise xylan backbones decorated with variable carbohydrate branches. As an alternative to acid extraction in industrial processes the combination of endo-1,4-β-xylanase and β-xylosidase can reduce xylan to xylose. However, unlike chemical extraction procedures enzyme systems can selectively hydrolyse α-L-arabinofuranosyl, 4-O-methyl-α-D-glucuronopyranosyl, acetyl and phenolic branches, and therefore have the potential to deconstruct hemicellulose whilst retaining desirable structural integrity and functionality. The sources, structures and catalytic activities of fungal xylanolytic enzymes are reviewed and discussed in the context of their biotechnological potential.